International Workshop on Advanced Imaging Technology (IWAIT) 2023 2023
DOI: 10.1117/12.2666465
|View full text |Cite
|
Sign up to set email alerts
|

A novel feature map compression method based on feature transformation for VCM

Abstract: In this paper, we propose a novel feature map compression method for Video Coding for Machines (VCM). The proposed method performs a principal component analysis (PCA)-based transform on feature pyramid network (FPN) feature maps using predefined basis and mean vectors. In addition, the proposed method reduces redundancy between different resolution levels within FPN feature maps based on redundancy between FPN layers. The fixed predefined basis and mean are employed through PCA with a set of training data set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Figure 2 showcases the overall pipeline of the proposed method. Similar to previous works [11][12][13][14], our method utilizes PCA to reduce the dimensions of the multi-level feature maps intended for compression. Previous methods pose certain drawbacks: they necessitate performing an independent PCA for one or more feature maps for each input datum during the encoding process, and they compress the basis In an effort to circumvent these issues, a transform-based feature map compression method employing a predefined generalized basis matrix and mean vector is proposed.…”
Section: Proposed Transform-based Feature Map Compression Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Figure 2 showcases the overall pipeline of the proposed method. Similar to previous works [11][12][13][14], our method utilizes PCA to reduce the dimensions of the multi-level feature maps intended for compression. Previous methods pose certain drawbacks: they necessitate performing an independent PCA for one or more feature maps for each input datum during the encoding process, and they compress the basis In an effort to circumvent these issues, a transform-based feature map compression method employing a predefined generalized basis matrix and mean vector is proposed.…”
Section: Proposed Transform-based Feature Map Compression Methodsmentioning
confidence: 99%
“…However, prior studies have indicated that the impact on performance from errors in the feature map domain due to quantization is not substantial [11]. Therefore, the previous feature map compression methods and the MPEG-VCM [22] feature anchor generation process adopted a uniform integer quantization method, relying only on the minimum and maximum values and bit depth [11][12][13][14].…”
Section: Quantization and Packingmentioning
confidence: 99%
See 3 more Smart Citations